Model pengembangan strategi pembelajaran berwawasan lingkungan bagipeserta praktik kerja industri siswa teknik mekanik otomotif - Sudarman Sudarman (Jurnal Pendidikan Vokasi, 2011)
LEARNING STRATEGY DEVELOPMENT MODEL ENVIRONMENTAL INSIGHT FOR PARTICIPANTS OF INDUSTRIAL WORK PRACTICES FOR AUTOMOTIVE MECHANICAL ENGINEERING STUDENTSThis study is the first phase of research that aims to examine the implementation of learning in tackling environmental problems SMK Skill Program of Otomotif Mechanic in building environmentally sound behavior. Research conducted in SMK N 1 Semarang and SMK N 7 Semarang. Retrieving data using the literature study and documentation. The analysis used is a description of the analysis. Description of the analysis results show that learning tackling environmental problems implemented wuth conventional strategies. From this description of finding result are then compiled design development model oriented/contextual learning strategies SETS (Environmenat, Science and Technology Community), models include: environmental teaching materials, unit of learning events and industry work practices certificate. Suggestions proposed: Should be testing the design strategy development model SETS insightful contextual learning, and then do the validation and continued dissemination.